Looking for Orion: literature at the interface of cosmopolitanism and translocation - Izarra, Laura (Aletria: Revista de Estudos de Literatura, 2009)
Resumo: Este ensaio apresenta a Literatura como um novo local, um espaço translocal, que consiste em vários espaços fraturados e conectados de conhecimentos. Usando como metáfora a escultura do artista irlandês Rowan Gillespie Looking for Orion analisarei como essa interconexão de espaços abre novos caminhos de representações literárias que compreendem não só as contradições internas da modernização (Theodor Adorno and Max Horkheimer), mas também outras formas de irregularidade e estranhamento que revelam estados da mente específicos não familiares com a racionalização. Ultrapassando as fronteiras dos textos literários na interface com língua, pintura, música, cinema e multimídia, farei uma re-visão dos velhos dramas sociais mundiais, como a fome, a migração e o nacionalismo desde um ponto de vista crítico multi-axial em que a literatura já é um espaço translocal institucional. É o espaço da memória e da imaginação que re-conta narrativas cosmopolitanas suspensas e mitos que estão abertos ao passado e ao presente. A arte da escrita se encontra num ponto de mutação ao interrogar “a imagem ‘eterna’ do passado” (Walter Benjamin), questões de identidade e subjetividade. Analisarei três contos como exemplo de confluência cosmopolitana: “Hunger” (1928) do escritor irlandês James Stephens, “Hunger” (1997) da escritora indiana Kamala Markandaya, e “The Chandelier” (2002) do escitor libanês-americano Gregory Orfaela.Palavras-chave: literatura; espaço translocal; leitura crítica multi-axial.Abstract: This essay discusses Literature as a new kind of location, a trans-location consisting of fractured and variously connected spaces of knowledges. Taking Rowan Gillespie’s sculpture “Looking for Orion” as a metaphorical starting point, I argue how that interconnection of spaces opens up alternative ways of literary representations that will apprehend not only the internal contradictions of modernization (Theodor Adorno and Max Horkheimer) but also other forms of unevenness and strangeness that disclose specific states of mind unfamiliar with rationalization. Moving beyond the edge of literary texts at the interface of language, painting, music, cinema, and multimedia sources, I would like to re-vision old world social dramas, such as the famine, migration, and nationalism from a multi-axial critical perspective in which literature is already an institutional translocation. It is the space of memory and imagination that retells cosmopolitan suspended narratives and myths that are open both to the past and the present. The art of writing is brought to a turning point questioning “the ‘eternal’ image of the past” (Walter Benjamin), issues of identity and subjectivity. I analyse three short stories as an example of cosmopolitan confluence: James Stephens’s “Hunger” (1928), Kamala Markandaya’s “Hunger” (1997) and George Orfaela’s “The Chandelier” (2002).Keywords: literature; translocation; multi-axial critical reading.